Helicobacter pylori Associated With Pulmonary Hemosiderosis. Issue 1 (January 2016) - Fujino, Hisanori; Takano, Yoshihiko; Tatsumi, Ako; Hida, Shinya; Sumimoto, Shinichi
Abstract : Supplemental Digital Content is available in the text.